Simulation-Based Design of a Low-Cost Broadband Wide-Beamwidth Crossed-Dipole Antenna for Multi-Global Navigational Satellite System Positioning - Songyuan Xu; Jiwon Heo; Won Seok Choi; Seong-Gon Choi; Bierng-Chearl Ahn (Sensors)
This paper presents the design of a wideband circularly polarized crossed-dipole antenna for multi-GNSS applications, covering the frequency range of 1.16–1.61 GHz. The proposed antenna employs orthogonally placed dipole elements fed by a three-branch quadrature hybrid coupler for broadband and wide gain/axial ratio beamwidth. The design is carried out using CST Studio Suite for a single dipole antenna followed by a crossed-dipole antenna, a feed network, and the entire antenna structure. The designed multi-GNSS antenna shows, at 1.16–1.61 GHz, a reflection coefficient of less than −17 dB, a zenith gain of 3.9–5.8 dBic, a horizontal gain of −3.3 to −0.2 dBic, a zenith axial ratio of 0.6–1.0 dB, and horizontal axial ratio of 0.4–5.9 dB. The proposed antenna has a dimension of 0.48 × 0.48 × 0.25 λ at the center frequency of 1.39 GHz. The proposed antenna can also operate as an LHCP antenna for L-band satellite phone communication at 1.525–1.661 GHz.